THE ROLE OF LAW IN ECONOMIC DEVELOPMENT RETAIL BUSINESS - Yuwafi, Rani (JILPR Journal Indonesia Law and Policy Review, 2024)
Indonesia's economic system, which is increasing in modern times, requires the Indonesian people to play an active role in improving their welfare and economic level. To improve the level of the economy, people open various kinds of businesses. One of his efforts is to open a retail business. Retail business is a business that sells goods and services to end users or distributed directly to consumers. The retail business in Indonesia is currently growing very rapidly along with the shift from traditional to modern lifestyles, therefore this golden opportunity is utilized by retailers who have large capital and good management skills to open retail business businesses such as mini markets, super markets, hypermarkets and and so on that allows people to shop with facilities and comfort as well as good service, besides that the price of each product is quite affordable.